Advantages Of Developing Linguistic Competencies In Students - Ergashev Doniyor Dovronovich (American Journal Of Social Sciences And Humanity Research, 2025)
The development of linguistic competencies in students has become one of the most crucial aspects of modern higher education. In today’s globalized and knowledge-based society, linguistic competence serves not only as a means of communication but also as a foundation for intellectual growth, critical thinking, and professional success. This article explores the advantages of developing linguistic competencies in students, highlighting their impact on academic achievements, intercultural communication, employability, and personal development. The research emphasizes the role of interactive methods, information technologies, and practice-oriented learning in fostering linguistic competence, ultimately preparing students to become competitive specialists in both national and international contexts.